2020
DOI: 10.1101/2020.11.14.382960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aversive Conditioning of Spatial Position Sharpens Neural Population-level Tuning in Visual Cortex and Selectively Reduces Alpha-band Activity

Abstract: Processing capabilities for many low-level visual features are experientially malleable, aiding sighted organisms in adapting to dynamic environments. Explicit instructions to attend a specific visual field location influence retinotopic visuocortical activity, amplifying responses to stimuli appearing at cued spatial positions. It remains undetermined, however, both how such prioritization affects surrounding non-prioritized locations, and if a given retinotopic spatial position can attain enhanced cortical r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Using EEG as a direct measure of visuocortical activity, numerous studies demonstrated converging evidence for enhanced sensory processing of threat-related features of visual stimuli. Mirroring the organization of visual receptive fields, threat-related sensory amplification has been reported for visual stimuli differing in orientation 10,11 , spatial frequency 12 , location 13 , and color 14 . However, enhanced visuocortical responses have also been observed for more complex visual stimuli, like geometric symbols 15,16 , pictures of virtual rooms 17 and facial identities 18,19 .…”
mentioning
confidence: 99%
“…Using EEG as a direct measure of visuocortical activity, numerous studies demonstrated converging evidence for enhanced sensory processing of threat-related features of visual stimuli. Mirroring the organization of visual receptive fields, threat-related sensory amplification has been reported for visual stimuli differing in orientation 10,11 , spatial frequency 12 , location 13 , and color 14 . However, enhanced visuocortical responses have also been observed for more complex visual stimuli, like geometric symbols 15,16 , pictures of virtual rooms 17 and facial identities 18,19 .…”
mentioning
confidence: 99%
“…Using EEG as a direct measure of visuocortical activity, numerous studies demonstrated converging evidence for enhanced sensory processing of threat-related features of visual stimuli. Mirroring the organization of visual receptive fields, threat-related sensory amplification has been reported for visual stimuli differing in orientation (McTeague et al, 2015;Miskovic & Keil, 2013), spatial frequency (Friedl & Keil, 2019), location (Friedl & Keil, 2020), and color (Boylan et al, 2019). However, enhanced visuocortical responses have also been observed for more complex visual stimuli, like geometric symbols (Stegmann et al, 2019;Wieser et al, 2016), pictures of virtual rooms (Kastner et al, 2015) and facial identities (Stegmann et al, 2020;Wieser et al, 2014).…”
Section: Introductionmentioning
confidence: 99%